2018
DOI: 10.1002/oby.22156
|View full text |Cite
|
Sign up to set email alerts
|

Accumulating Data to Optimally Predict Obesity Treatment (ADOPT): Recommendations from the Biological Domain

Abstract: The accumulation of data on key biological factors, along with behavioral, psychosocial, and environmental factors, can generate a more precise description of the interplay and synergy among them and their impact on treatment responses, which can ultimately inform the design and delivery of effective, tailored obesity treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 100 publications
0
23
0
Order By: Relevance
“…Each domain subgroup considered the following criteria to guide their selection of high‐priority constructs and measures: (1) the strength and source of the current evidence related to weight‐loss outcomes or weight‐related behaviors (e.g., randomized clinical trial versus observational data), (2) the quality of the measure (e.g., validity and reliability), (3) the feasibility of using the measure within a clinical trial (e.g., cost, researcher expertise requirements, logistics), and (4) the participant burden posed by the measure (e.g., administration time, invasiveness). Although the entire working group was presented with this list of criteria for consideration, the four domain subgroups were given a considerable amount of flexibility in how they weighed each criterion and the process by which their domain curated the recommended set of core measures .…”
Section: The Adopt Core Measures Working Group: Process Constructs mentioning
confidence: 99%
See 2 more Smart Citations
“…Each domain subgroup considered the following criteria to guide their selection of high‐priority constructs and measures: (1) the strength and source of the current evidence related to weight‐loss outcomes or weight‐related behaviors (e.g., randomized clinical trial versus observational data), (2) the quality of the measure (e.g., validity and reliability), (3) the feasibility of using the measure within a clinical trial (e.g., cost, researcher expertise requirements, logistics), and (4) the participant burden posed by the measure (e.g., administration time, invasiveness). Although the entire working group was presented with this list of criteria for consideration, the four domain subgroups were given a considerable amount of flexibility in how they weighed each criterion and the process by which their domain curated the recommended set of core measures .…”
Section: The Adopt Core Measures Working Group: Process Constructs mentioning
confidence: 99%
“…The ADOPT Core Measures that were selected from the behavioral , biological , environmental , and psychosocial domains are organized by domain in Table . More details about the selection of each domain's constructs and measures are found in the domain‐specific papers that accompany this overview.…”
Section: The Adopt Core Measures Working Group: Process Constructs mentioning
confidence: 99%
See 1 more Smart Citation
“…In an implementation science framework, using the simplest and most practical measures customized to individual study and patient needs is a key. One promising development in obesity research is standardizing measurement across studies and developing core measures through a project known as Accumulating Data to Optimally Predict Obesity Treatment (ADOPT), which published six papers in Obesity in Spring, 2018 . By focusing on standardized activities and measures to prevent weight gain, patients with obesity may manage potential health harms individually, with a better understanding of maintaining lifestyle modifications long term.…”
Section: Issues and Potential Solutionsmentioning
confidence: 99%
“…Each domain's subgroup reviewed variables measured in adult weight loss trials and identified the current gold standard assessment method used to measure those variables. The four companion papers further discuss the identification and selection process of the variables, or “core” constructs, measures, the associated critical knowledge gaps, and limitations of available assessment tools within each domain.…”
mentioning
confidence: 99%